2017
DOI: 10.1155/2017/4856276
|View full text |Cite
|
Sign up to set email alerts
|

The Role of EUS-BD in the Management of Malignant Biliary Obstruction: The Indonesian Perspective

Abstract: Aims To evaluate the success rate and related factors of endoscopic ultrasound guided-biliary drainage (EUS-BD). Material and Methods We conducted a retrospective study among 24 patients with malignant biliary obstruction who underwent EUS-BD after failed ERCP from January 2015 to December 2016 in a tertiary health center. The bilirubin levels before and after the procedure were used to define the clinical success rate, while the stent deployment was used to define the technical success rate. We placed either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Currently, EUS-BD is not the first-line management of malignant biliary obstruction in Indonesia or most developing Asian countries. Many studies have shown the advantage of performing EUS-BD after a failed ERCP cannulation [12, 13, 14, 15]. However, EUS-BD requires high levels of experience and technique as most studies were performed in highly expert centers.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, EUS-BD is not the first-line management of malignant biliary obstruction in Indonesia or most developing Asian countries. Many studies have shown the advantage of performing EUS-BD after a failed ERCP cannulation [12, 13, 14, 15]. However, EUS-BD requires high levels of experience and technique as most studies were performed in highly expert centers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, EUS-CDS is not suitable for proximal (hilar) biliary obstruction, where an intrahepatic EUS-BD approach is required. In the specific situation of hilar malignancy EUS-guided HGS was found to be safe and effective[52,53], although the duration of efficacy was limited[40] and lower clinical success rates were demonstrated than for distal obstruction[41].…”
Section: Indicationsmentioning
confidence: 99%
“…[ 5 ] Therefore, EUS-BD is a therapeutic option that can be applied as initial drainage or for reintervention. [ 6 7 8 9 10 11 12 13 14 ] The alternative to EUS-BD drainage is percutaneous transhepatic drainage. Studies have shown a similar success rate, but EUS-BD drainage seems to have more advantages with lower rates of intervention.…”
Section: Introductionmentioning
confidence: 99%